Effects of meal size and proximal-distal segmentation on gastric activity - Americo, Madileine F. [UNESP]; Ietsugu, Marjorie V. [UNESP]; Romeiro, Fernando Gomes [UNESP]; Cora, Luciana A.; Oliveira, Ricardo B.; Miranda, Jose Ricardo A. [UNESP] (Baishideng Publ Grp Co Ltd, 2010)
AIM: To evaluate the effects of meal size and three segmentations on intragastric distribution of the meal and gastric motility, by scintigraphy.METHODS: Twelve healthy volunteers were randomly assessed, twice, by scintigraphy. The test meal consisted of 60 or 180 mL of yogurt labeled with 64 MBq (99m)Tc-tin colloid. Anterior and posterior dynamic frames were simultaneously acquired for 18 min and all data were analyzed in MatLab. Three proximal-distal segmentations using regions of interest were adopted for both meals.RESULTS: Intragastric distribution of the meal between the proximal and distal compartments was strongly influenced by the way in which the stomach was divided, showing greater proximal retention after the 180 mL. An important finding was that both dominant frequencies (1 and 3 cpm) were simultaneously recorded in the proximal and distal stomach; however, the power ratio of those dominant frequencies varied in agreement with the segmentation adopted and was independent of the meal size.CONCLUSION: It was possible to simultaneously evaluate the static intragastric distribution and phasic contractility from the same recording using our scintigraphic approach. (C) 2010 Baishideng. All rights reserved.
Keywords: Gastric motility; Phasic contractions; Proximal stomach; Scintigraphy; Meal size